Pemanfaatan Augmented Reality Sebagai Media Inovatif Dalam Pembelajaran IPAS Untuk Melestarian Sumber Daya Alam - Taufik Afandi; Umi Mahmudah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to explore the effectiveness of using Augmented Reality (AR) technology as an innovative medium in learning Natural and Social Sciences (IPAS) to increase elementary school students' awareness and understanding of preserving natural resources. This research uses a quasi-experimental research method with a pretest-posttest control group design. The research subjects were fifth grade students at an elementary school in Indonesia, who were divided into an experimental group that used AR media and a control group that used conventional learning media. The research results show that the use of AR media significantly increases students' understanding of the concept of preserving natural resources compared to traditional learning methods. In addition, students in the experimental group showed higher levels of learning motivation as well as active participation in class discussions. The implication of this research is that AR technology can be an effective and interesting learning tool in teaching complex environmental topics. The use of AR not only helps students understand concepts visually and interactively, but also motivates them to be more actively involved in efforts to conserve natural resources. The results of this research provide a basis for the development of technology-based learning media that can be applied in various educational contexts, especially to support sustainable education at the elementary school level.